Assessment of oral health status among occupational chefs and pantry workers in Hyderabad city - Velthuru Srujan Kumar; Siva Kumar Patanapu; Chilukuri Sai Sreeja; Shiva Prasad Kyasanoor; Nagarani Veeraboina; Nitya Krishna Nanamadri (Journal of Education and Health Promotion)
BACKGROUND: The chefs and pantry workers environment plays a crucial role in the general and oral health. These workers have some unusual work timings and have a lot of stress and anxiety, and they also consume tobacco, alcohol, and smoke the cigarettes, which has a greater impact on oral health. MATERIAL AND METHODS: A total of 86 kitchen workers (53 chefs and 33 pantry workers) of ten well-known restaurants in Hyderabad city were included. In clinical oral examination, oral hygiene status was assessed using Simplified-Oral Hygiene Index (OHI-S) along with demographic details. Dentition status, periodontal condition, and loss of attachment (LOA) according to WHO criteria 2013. The collected data were analyzed using the Statistical Package Social Sciences (SPSS) package version 21.0. Statistically significance was set at P < 0.05. RESULTS: Age-wise comparison of mean OHI-S scores among chefs and pantry workers reported that all age groups among chefs had significantly higher mean scores compared to workers (P = 0.0001*) for the same age group. When periodontal health status of the study population was considered, chefs of all age groups reported a poor periodontal health with significantly high LOA scores compared to workers except for the age group 25–35 years (P = 0.0001*). Both males and females in the chef group had significantly higher scores for all the oral parameters compared to workers (OHI-S, DMFT, gingival status, periodontitis, and LOA) (P = 0.0001*). CONCLUSION: The results of this study show that kitchen workers (chefs and pantry workers) in the community do suffer from various oral health problems such as dental caries and periodontal problems.